2014
DOI: 10.3928/01477447-20140225-07
|View full text |Cite
|
Sign up to set email alerts
|

Popliteomeniscal Fascicle Tears

Abstract: Isolated popliteomeniscal fascicle tears are often unrecognized and misdiagnosed. Patients typically have vague symptoms and often-normal magnetic resonance imaging and physical examination findings. Isolated injuries are often misdiagnosed and mistreated, leading to delayed surgical treatment. Unrecognized tears can lead to continued disability, lateral meniscus tears, and chondral lesions. Appropriate diagnosis and treatment with inside-out lateral meniscus repair will allow the athlete to return to activity. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…The oldest study was published in 1988 [33] and the newest one in 2023 [7] and more than half of the studies were from the past 10 years. Regarding the study design, all of the articles were descriptive, of which 12 studies were case reports [3,8,11,12,17,29,34,35,[40][41][42][43] and eight were case series [7,19,22,24,31,33,49,53]. Therefore, all studies had a level of evidence of IV according to the Oxford Center of Evidence-Based Medicine criteria.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The oldest study was published in 1988 [33] and the newest one in 2023 [7] and more than half of the studies were from the past 10 years. Regarding the study design, all of the articles were descriptive, of which 12 studies were case reports [3,8,11,12,17,29,34,35,[40][41][42][43] and eight were case series [7,19,22,24,31,33,49,53]. Therefore, all studies had a level of evidence of IV according to the Oxford Center of Evidence-Based Medicine criteria.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…HLM is usually underdiagnosed due to unspecific symptoms and often a normal physical examination and magnetic resonance imaging (MRI) of the afflicted patients [2,3,38,47]. Unlike routine knee examinations, which reveal no abnormalities, it is reported that placing the patient's knee in the figureof-4 position can reproduce the same symptoms, helping to confirm the HLM diagnosis [3]. In addition, MRI is usually interpreted as normal in HLM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A pesar de los avances en el conocimiento de este tipo de lesiones, la evaluación mediante artroscopia sigue siendoen la actualidad el gold standard para el diagnóstico de certeza, puesto que permite una visualización directa de los fascículos poplíteo-meniscales y la evaluación de la movilidad del menisco lateral. 13 Existen múltiples técnicas quirúrgicas publicadas para el tratamiento de este tipo de patología: meniscectomía, 14 reduccióntérmica meniscal, 15,16 reparación con sutura meniscal en forma abierta 9 y artroscópica, 17,18 además reconstrucción de fascículos poplíteomeniscales con utilización de injerto. 1 Dado lo poco frecuente del Síndrome de Menisco Hipermóvil, el propósito de esta publicación es describir nuestra experiencia en el diagnóstico y tratamiento de este tipo de lesiones dentro de un grupo de traumatólogos especialistas en rodilla, en relación a 9 casos clínicos.…”
Section: Introductionunclassified